GsLRPK, a novel cold-activated leucine-rich repeat receptor-like protein kinase from Glycine soja, is a positive regulator to cold stress tolerance - Yang, Liang (Plant science : an international journal of experimental plant biology, 2014)
Copyright © 2013 Elsevier Ireland Ltd. All rights reserved.